Implications for Variability of Practice from Pedagogy and Motor Learning Perspectives: Finding a Common Ground - Boyce, B. A.; Coker, C.; Bunker, L. K. (Quest, 2006)
The discourse contained in this article is the result of an on-going discussion about "providing variability of practice" between professionals from different areas of study within kinesiology. The impetus for this discussion arose from a lack of common terminology, differing views, and the sometimes contrasting research and professional practices promoted in the areas of pedagogy and motor learning. Since many undergraduate and graduate level students enroll in courses in both motor learning and pedagogy, it is imperative that professionals seek a common ground that leads to an understanding of the areas where the two perspectives converge or differ. A question and answer format, from the viewpoints of pedagogy and motor learning, was used to guide the discussion related to variability of practice and its research and practical applications in the teaching and learning process of motor skills.